STRATEGI BISNIS PT NURINDO WISATA DALAM MELAKUKAN REKRUTMEN JAMAAH - Siti Nurbayah (Institut Agama Islam Negeri Metro, 2022)
The primary issue addressed in this study is PT Nurindo Wisata hajj business strategy in recruiting prospective pilgrims. This type of research is qualitative, and the research method used is a management approach. Field research data collection techniques include observation, interviews, and documentation. The findings of this study indicate that PT Nurindo Wisata hajj business strategy has business strength in attracting prospective pilgrims by implementing a differentiation strategy, namely the Solution Program. PT Nurindo Wisata innovates in the marketing of Hajj products, specifically with a reference system that is distinct from the MLM system. The promotion is carried out by maintaining contact and then making a presentation.